ENGLISH STUDENTS’ SKILL (THIRD SEMESTER) AT UNIVERSITY OF PASIR PENGARAIAN IN FINDING OUT MORAL VALUE IN NARRATIVE TEXT - Pipit Rahayu (International Conference on Languages and Arts, 2014)
The Purpose of this Research was to know the skill of the Third Semester Students of English Study Program in University of PasirPengaraianin finding out moral value in narrative text. In narrative text there should be positive and negative massages that make students learn more about the characters’ behavior. The massage is about the rightness or wrongness of what common people say as moral value. It is what should be done and what should not be done, what is good or bad. The participants of this Research were the Third Semester students of English Study Program at University of PasirPengaraian, RokanHulu, Riau. This class consisted of 27 students. The research was conducted from October 2013 to January 2014.  The method of this research is descriptive research.To collect the data in the present study, the writer decided to use reading test in written form. The Instrument test include Fable, Legend and Fairy Tale. Based on the data analysis, it can be concluded thatsome students were still confused in finding out Moral Value in Narrative Text. It can be seen from the Percentage of students’ skill. First, students who was in poor to average level skill are 7,40% (2 students).Second, students who was in average to good level skill are 85,20% (23 students). Third, Students who was in Good to Excellent level are 7,40% (2 students). In addition, The Third semester students’ skill in finding out Moral Value in Narrative text was in Average skill.   Keywords: Third semester students’skill, Narrative text, Moral Value